All These Worlds Are Yours, Except India : The Effectiveness of Export Subsidies in Nepal - Defever, Fabrice; Reyes, Jose Daniel; Riano, Alejandro; Varela, Gonzalo (World Bank, Washington, DC, 2017)
This paper evaluates the effect on firm-level export outcomes of the Cash Incentive Scheme for Exports program provided by the Government of Nepal. The analysis utilizes customs-level data for 2011-14, combined with information on the subsidy payments made to individual firms provided by the Central Bank of Nepal. The Cash Incentive Scheme for Exports cash subsidy is available to firms exporting a select group of products, and requires firms to export to countries other than India. Overall, the subsidy has not produced a significant impact on firm-level export values, prices, quantities, or their growth rates. However, the study finds a small positive effect on the number of eligible products exported to countries other than India and the number of destination markets reached among firms that receive the subsidy. These results are consistent with the fact that the subsidy was granted primarily to large exporters that were already shipping eligible products to countries other than India. The findings suggest that although the cash subsidy has not produced a significant increase in exports, it has achieved a positive impact on export diversification for firms that were already satisfying the scheme's eligibility criteria.